Embodied Energy in Export Flows Along Global Value Chain: A Case Study of China’s Export Trade - Zhang, Boya; Bai, Shukuan; Ning, Yadong (Frontiers in Energy Research, 2021)
The energy issue is closely related to the development of human society and the economy. In the context of the deepening development of economic globalization and the increasing prosperity of international trade, embodied energy is considered as an indicator that can more comprehensively reflect the nature of a country's energy use than the direct energy use. The development of trade in value-added accounting and global value chain theory has brought new ideas to embodied energy research. This paper applies the trade in value-added accounting to the study of embodied energy, and establishes a complete framework to decompose the sources, destinations, and transfer routes of embodied energy in China's export, and depicts the embodied energy flows in China's exports in detail at the country and sector levels. The results show that China's gross export and embodied energy has maintained a decoupling state during the whole study period, while the domestic energy and value-added embodied in export didn’t decouple in some years according to the value-added accounting. And the structure of export products still needs to be improved. At the country level, the embodied energy flows in intermediate and final products to different importers vary greatly, and the embodied domestic energy intensity of intermediate exports to different importers also shows great differences. At the sector level, there is a mismatch between the sectors that export products and that actually consume energy. And this paper calls for more research to depict international trade embodied energy in detail, and pay attention to the differences between forward-linkage and backward-linkage measures at the sector level analyses.